CONTROLLED ENZYMOLYSIS PREPARATION OF NANOCRYSTALLINE CELLULOSE FROM PRETREATED COTTON FIBERS - Xiaoquan Chen,; Xueyan Deng,; Wenhao Shen,; Lingling Jiang (BioResources, 2012)
Natural cotton fibers were pretreated with DMSO, NaOH, or ultrasonic waves and hydrolyzed by cellulase (Trichoderma vride G) to prepare nanocrystalline cellulose (NCC). The as-prepared samples were characterized by TEM, DLS, XRD, and FT-IR. The influences of the pretreatment on the yield and morphology of NCC were investigated. The alterations of the crystalline phase and chemical structure of NCC were also measured during the enzymolysis process. The experimental results proved that the pretreated cotton fibers could be hydrolyzed by the Trichoderma cellulase to prepare a nanosized strip (10 to 40 nm x 70 to 280 nm) and grainy (20 nm or 6 nm) crystalline cellulose, in which the different morphologies resulted from the different manners of pretreatment. The unaltered crystalline phase and chemical composition of NCC prepared by enzymolysis of pretreated cotton fibers were measured. The highest yield of NCC reached was 32.4%.